Educational program â€œUse of Denturesâ€ in Kaligawe Village Community - Benni Benyamin; R. Rama Putranto; M. Dian Firdausy; Avisa Aura Nisa (ABDIGI : JURNAL PENGABDIAN MASYARAKAT KESEHATAN GIGI, 2024)
Problems in Kaligawe Village related to the lack of knowledge of the community, especially the elderly, about denture materials (acrylic, valplas, and metal) and proper care are a challenge in dental health. This lack of understanding leads to poor decisions in choosing dentures, which affects comfort, durability, and price. In addition, improper care of dentures can lead to infection and damage to oral tissues. Health counseling and two-way discussions in small groups were used as methods to improve this knowledge. This method proved effective in providing a more in-depth and interactive understanding, allowing older adults to understand the advantages and disadvantages of different denture materials and the importance of proper care. Studies show that direct interaction in small groups helps older adults remember information better and improves their quality of life. In conclusion, this increased understanding through education enables people to make better choices in using dentures, which has a positive impact on their health and quality of life.Keywords: education, denture materials; dental health; interactive discussion